A Decision Support Model for Prequalifying IPD Project Participants in Construction Projects - El Masri, Ahmad (2022)
A Master of Science thesis in Construction Management by Ahmad El Masri entitled, “A Decision Support Model for Prequalifying IPD Project Participants in Construction Projects”, submitted in November 2022. Thesis advisor is Dr. Sameh El-Sayegh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).